1990
DOI: 10.1016/0014-5793(90)81171-j
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inhibitor binding in HIV‐1 protease and in non‐viral aspartic proteases: the role of the flap

Abstract: The crystal structure of HIV-l protease with an inhibitor has been compared with the structures of non-viral aspartic proteases complexed with inhibitors. In the dimeric HIV-l protease, two 4-stranded /?-sheets are formed by half of the inhibitor, residues 27-29, and the flap from each monomer. In the monomeric non-viral enzyme the single flap does not form a/I-sheet with an inhibitor. The HIV-l protease shows more interactions with a longer peptide inhibitor than are observed in non-viral aspartic protease-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
4

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 20 publications
2
42
0
4
Order By: Relevance
“…Moreover, the experimentally determined cleavage rates of the cleavable peptides agreed well with the CRM predicted rates on HXB2 and mutated HIV-1 proteases (68% accuracy; RMSEP ¼ 1.01; Figure 1B). Addition of all experimental data to the CRM further increased CRM (Table 3, numbers [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Shown is the predicted versus experimentally determined cleavage rates by HXB2 (red) and mutant HIV-1 proteases, I84V (blue), L90M (magenta), and I84 þ L90M (green).…”
Section: Author Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the experimentally determined cleavage rates of the cleavable peptides agreed well with the CRM predicted rates on HXB2 and mutated HIV-1 proteases (68% accuracy; RMSEP ¼ 1.01; Figure 1B). Addition of all experimental data to the CRM further increased CRM (Table 3, numbers [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Shown is the predicted versus experimentally determined cleavage rates by HXB2 (red) and mutant HIV-1 proteases, I84V (blue), L90M (magenta), and I84 þ L90M (green).…”
Section: Author Summarymentioning
confidence: 99%
“…Because retroviral proteases are inherently dynamic structures that undergo significant structural changes with binding, we described each structurally aligned amino acid of the 61 retroviral proteases by their principal physicochemical properties (i.e., their z-scales z 1 -z 5 ), rather than using the proteins' static 3-D structures (see Materials and Methods, Figure S1, and Table S2) [15,16]. Similarly, we described the retroviral protease substrates by considering the same principal physicochemical properties of every single amino acid of the octapeptide sequence spanning the P 4 to P 4 9 position (see Materials and Methods for details).…”
Section: Introductionmentioning
confidence: 99%
“…Wat 301, which has been observed in all other inhibitor complexes, makes contacts with the carbonyl oxygens of residues at the P2 and P1' positions, and with the NH groups of residues Ile 50 and Ile 150 on the flaps, thus completely satisfying its hydrogen-bonding capacity. This water molecule possibly plays a crucial role in inducing the fit of the flaps over the inhibitor (Gustchina & Weber, 1990). The ND1 of histidine in the P2 position acts as a hydrogen-bond donor to the main-chain carbonyl oxygen of Gly 48 on the flap.…”
Section: I F O Imentioning
confidence: 99%
“…In the crystal structure of HIV PR with different inhibitors, a conserved water molecule is observed that forms a tetrahedral set of interactions with P, C=O, P,' C=O of the inhibitor, and NH of He50 and Ile50' from the tip of the protease flaps [3].…”
Section: Hydrolysis Of Oligopeptides Representing Other Naturally Occmentioning
confidence: 99%